2021
DOI: 10.3233/jad-201396
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Association Between Increase of Behavioral and Psychological Symptoms of Dementia During Lockdown and Caregivers’ Poor Mental Health

Abstract: Background: From March 2020, the support and care systems for caregivers and people with dementia (PWD) were suspended or dramatically changed due to the lockdown during the world pandemic of COVID-19. Thus, these changes in living conditions have had deleterious consequences on the behavior of PWD and subsequently on their caregivers’ mental health, the two being linked. Objective: Our study aimed to examine changes in behavior among PWD and to look for associations between the evolution of behavioral and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 34 publications
3
57
0
2
Order By: Relevance
“… 4913 Structured interview 1 month after beginning of quarantine NR 59% Worsening of existing symptoms: 51% New onset of symptoms: 26% (Irritability, apathy, agitation most commonly reported) NR 27% (type of change no reported) 6 Pogan et al. 26 ] France Community. 389 Survey During the first lockdown (April to June 2020) NR 43% NR NR 6 Cohen et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 4913 Structured interview 1 month after beginning of quarantine NR 59% Worsening of existing symptoms: 51% New onset of symptoms: 26% (Irritability, apathy, agitation most commonly reported) NR 27% (type of change no reported) 6 Pogan et al. 26 ] France Community. 389 Survey During the first lockdown (April to June 2020) NR 43% NR NR 6 Cohen et al.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies in this review reported large percentages of people living with dementia that experienced exacerbation or new onset of BPSD. Nine studies reported more than 40% of participants experiencing a worsening of exisiting symptoms or onset of new ones (ranging 42–75%) [ 11 , [21] , [22] , [23] , [25] , [26] , [27] , [28] , [29] ]. The majority of studies named depression, anxiety and apathy as the symptoms aggravated the most during lockdowns.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, despite the fact that care providers differ in their working style, motivations, and aims between formal and informal caregivers, COVID-19 brought about overlapping responsibilities and a shift in roles that led both populations of caregivers to experience increased and imbalanced care distribution that negatively affected their mental well-being [ 33 , 34 ]. They were not only exposed to higher levels of stress, anxiety, and depression [ 35 , 36 ], but also equally revealed sleep disturbances [ 37 ], frustration, and hopelessness during their caregiving roles, with the consequent risk of struggling with negative emotions, such as self-criticism and shame [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social distancing measures related to the COVID-19 pandemic, such as home confinement and restrictions on visitors for nursing home residents, imposed a risk for social isolation and/or loneliness and they limited physical activity for people with dementia [ 16 ]. This has been shown to negatively impact neuropsychiatric symptoms, such as anxiety and depression [ 17 - 19 ], in people with dementia and to cause further cognitive and functional decline [ 17 , 20 ]. However, some nursing home residents in the Netherlands were reported to have decreased neuropsychiatric symptoms, such as agitation and aggression, due to a reduction in overstimulation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%